Nursing Students' Health Beliefs and Attitudes Towards Thalassemia Screening - Feriana Ira Handian; Neni Maemunah; Ziu Kipply; Aisah Aisah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Approximately 2,500 newborns are born with thalassemia annually in Indonesia. Premarital screening can help avoid thalassemia. Health behavior is expected to be influenced by individual views about the disease, and nurses can affect health beliefs by serving as a model for the community. The purpose of this study is to examine the association between nursing students' attitudes toward thalassemia screening and their health beliefs as future nurses. In July 2025, a cross-sectional survey of 122 respondents, was conducted among participants aged 18 to 24. Simple random sampling was used to choose the sample. A questionnaire that the researcher had been tested for validity and reliability was used to gauge screening attitudes and health beliefs. The Pearson correlation test was then used to examine the data statistically. Of the respondents, only 24.59% had undertaken initial screening with Hb examination, and the majority (75.41%) had never done so. The results showed a significant relationship between health beliefs and attitudes toward thalassemia screening (p-value 0.001). In the future, developing a thalassemia screening education program based on culture and health beliefs is necessary to increase participation in thalassemia screening. Nurses should be trained to develop educational programs based on health beliefs to maximize their ability to provide interventions for at-risk groups.Â